2019
DOI: 10.1002/ffj.3486
|View full text |Cite
|
Sign up to set email alerts
|

Combination of 13C and 2H SNIFNMR isotopic fingerprints of vanillin to control its precursors

Abstract: Synthetic vanillin is the flavouring most used in agro‐food industries, but more and more frequently consumers are now turning to natural origin. Vanilla planifolia (Andrews) is the most commercialized species of pods in the world and is mainly produced in Madagascar. However, periodically the production of V. planifolia suffers from poor climatic conditions, with the resulting degradation of both the quality and the quantity of the pods. Consequently, the price of vanilla pods rose to record in 2017 and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 49 publications
(134 reference statements)
2
32
0
Order By: Relevance
“…A cheap source of vanillin enriched in 13 C will make it easier to simulate the  13 CBulk value of vanillin from vanilla pods by mixing vanillin from the respective sources, which can increase the risk of fraud being perpetrated while remaining unnoticed by the analysis of  13 CBulk values. However, several studies on purified vanillin have demonstrated that additional information about the  2 H values as well as positionspecific isotope analysis of stable hydrogen and carbon enables the distinction of vanillin obtained from different precursors even if the  13 CBulk ranges overlap (Geißler et al, 2017;Tenailleau, Lancelin, Robins, & Akoka, 2004;Guyader et al, 2019).…”
Section: Analysis Of  Cbulk Value Of Vanillin Derived From Glucosementioning
confidence: 99%
See 3 more Smart Citations
“…A cheap source of vanillin enriched in 13 C will make it easier to simulate the  13 CBulk value of vanillin from vanilla pods by mixing vanillin from the respective sources, which can increase the risk of fraud being perpetrated while remaining unnoticed by the analysis of  13 CBulk values. However, several studies on purified vanillin have demonstrated that additional information about the  2 H values as well as positionspecific isotope analysis of stable hydrogen and carbon enables the distinction of vanillin obtained from different precursors even if the  13 CBulk ranges overlap (Geißler et al, 2017;Tenailleau, Lancelin, Robins, & Akoka, 2004;Guyader et al, 2019).…”
Section: Analysis Of  Cbulk Value Of Vanillin Derived From Glucosementioning
confidence: 99%
“…Another analytical technique for the authentication of vanillin is the determination of 13 C and 2 H-SNIF-NMR isotopic fingerprints. Recently, vanillin ex ferulic acid (corn) has also been included in a database where vanillin from different precursors (ferulic acid (rice), eugenol, cucurmin, lignin, guaiacol, vanilla pods) were investigated (Guyader et al, 2019). The 13 C isotopic profiles allowed a promising distinction of all of the precursor groups.…”
Section:  13 C and  2 H Analyses Of Bulk Vanillin And Vanillin Methmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to magnetization transfer from the sensitive proton to the coupled carbon an improvement in the sensitivity was achieved. Furthermore, by means of INEPT the precision of the order of 1‰ was able to be reached [ 82 , 85 ].…”
Section: Nmr Techniques Used For Determination Of Authenticity Of mentioning
confidence: 99%